Quality of life in Indian women with fertility problems as assessed by the FertiQoL questionnaire: a single center cross sectional study - Hema Jagdish Desai; Sirisha Rao Gundabattula (Taylor & Francis Group, 2019)
Purpose: Infertility and its treatment can significantly impact an individual's physical and psychological health; however, this has not been well-studied in the Indian population. This study aimed to assess the quality of life in women with infertility at a teaching hospital in Hyderabad, India. Methods: In this cross sectional study of women with infertility, the quality of life was measured using the 'FertiQoL International' questionnaire (English/Hindi). Results: The age ranged from 20 to 38 years and polycystic ovary syndrome was the most common cause of infertility. Core FertiQoL scores were analyzed in 215 women and Treatment FertiQoL in 156. The mean Total FertiQoL score in the study population was 66.1 (SD 13.0) and this overall score was not influenced by socio-demographic or infertility-specific factors. However, on subscale analysis, women who had living children and were university-educated had significantly better emotional scores while obese (≥35 kg/m2) women and those on ovulation induction treatment had poorer mind body and relational scores, respectively. Women with associated co-morbidities had worse quality of life on the Treatment Environment scale than those without. Conclusions: The results provide a baseline quality of life score in these women. Infertility had the greatest impact on the emotional domain.